The preliminary study suggests an association between NF-ĸB pathway activation and increased plasma 20S proteasome activity in intracranial aneurysm patients - Joanna Kamińska; Marzena Tylicka; Kinga Sutkowska; Karolina Marta Gacuta; Magdalena Maria Sawicka; Ewa Kowalewska; Magdalena Ćwiklińska-Dworakowska; Mateusz Maciejczyk; Tomasz Łysoń; Johannes Kornhuber; Piotr Lewczuk; Joanna Matowicka-Karna; et al. (Scientific Reports, 2024)
Abstract The significant role of increased activation of 20S proteasomes in the development of abdominal aortic aneurysms has been well-established in a mouse model. The available literature lacks similar studies concerning brain aneurysms. The aim of the study was to verify the hypothesis that patients with unruptured intracranial aneurysms (UIA) have increased 20S proteasome ChT-L activity compared to the control group of individuals without vascular lesions in the brain. In the next step, the relationship between the activity of 20S proteasomes ChT-L and precursor proteins from the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) family, namely NF-κB1 (p105), NF-κB2 (p100), NF-κB p65, and the inflammatory chemokine MCP-1, was examined. Patients with UIA had significantly higher 20S ChT-L proteasome activity compared to the control group. Patients with multiple aneurysms had significantly higher 20S proteasome ChT-L activity compared to those with single aneurysms. In patients with UIA, the activity of the 20S proteasome ChT-L negatively correlated with the concentration of NF-κB1 (p105) and NF-κB p65 precursor proteins and positively correlated with the concentration of the cerebrospinal fluid chemokine MCP-1. Our results may suggest that increased 20S proteasome ChT-L activity in UIA patients modulates inflammation in the cerebral arterial vessel via the MCP-1 chemokine as a result of activation of the canonical NF-κB pathway.